ReduxGO: Context-Aware Mobile Recommender Application for Reducing Stop-and-Go Scenario - Haron, N. (IEEE Computer Society, 2017)
There are many technologies and applications available that can be used to assist driver to avoid traffic congestion. However, most of the current applications are emphasizing on giving current updates to drivers to avoid the congested area. Based on prior research, the stop-and-go traffic scenario is one of the main causes of heavy traffic jams. However, there is no specific application that can assist the driver to reduce the stop-and-go traffic condition. Therefore, we propose a mobile application based on context-aware recommender system to aid driver in deciding the right speed to alleviate the stop-and-go scenario. This paper describes the design and implementation of the mobile application called ReduxGO. We have evaluated the application using Technology Acceptance Model (TAM) and the results yield the users' perceptions towards using the application. © 2016 IEEE.